Free Will, Subjectivity and the Physics of the Nervous System - Ceroni, Mauro; Prosperi, Giovanni Maria (Scientific Research, 2018)
We want to stress the irreducibility of subjectivity to a pure physical process and, related to this the existence of an actual free will. A discussion on the existence of free will goes back at least to the Middle Ages. Today however the problem has been considered again in the framework of Neurophysiology and in connection with specific experiments. The problem is related to reductionism, i.e. the claim that subjectivity could be considered an epiphenomenon of the cerebral processes, the argument being that all our sensorial perceptions, the control of movement, our states of wakefulness or of unconsciousness can be related to the activation or to the block of specific areas of our cerebral cortex. In the frame of this conception free will is denied essentially on the basis of physical determinism. In contrast to such attitude, we argue that experiences like consciousness of ourselves, of a personal identity or even simply of qualia completely escape from concepts of physical nature. As a consequence of the specific epistemological choice, they cannot even be expressed in the language of Physics. The point of view of Physics and introspection appear both essential but complementary and irreducible one to the other; any attempt to do so brings to unresolvable aporias. Specifically on free will, we note that our nervous system is a complex mesoscopic system, for an understanding of its occurrences, reference to Quantum Theory is essential. As consequence, its reaction to any external input is not uniquely determined but is open to a plurality of responses for which only a distribution of probability is given. Physics does not provide any cause for one response rather than another, while we experience our response to be intentional. Quantum Mechanics seems to offer the logical space to reconcile Physics with introspection. Some basic notions on the structure and working of neurons and of the central nervous systems are also recalled, Liebet’s experiments on retarded awareness and the role of free will in the knowledge process are discussed.
Keywords: Free Will; Cerebral Processes; Reductionism; Subjective Perceptions; Mind; Introspection; Quantum Mechanics